Smart modeling of flood occurrences in a river basin - Mohammed, Thamir Ahmed; Said, Salim; Bardaie, Mohd Zohadie; Basri, Shahnor (Universiti Putra Malaysia, 1999)
In the last few decades there have been a proliferation of researches which use smart technologies in field of water resources such as water supply, irrigation, flood mitigation and water quality control. Smart technologies use the advances in science and technology for economical and efficient design, operation and maintenance in various projects. Development in computer technology and numerical methods of solution has led to increasing interest in applying the smart modelling in surface water hydrology. Shortage of recorded hydrologic data (streamflow and rainfall) is considered as another factor which encourage researchers to use the mathematical models (smart modelling) as a tool in flood studies. Shortage of the streamflow and rainfall records are often encountered in parts of river basin which are located in the agriculture and remote rural areas. At the same time the collection of such data is costly, difficult and time consuming. During flooding, severe damage will occur to the agricultural lands or farms and the availability of a good hydrologic record will help in taking the required protection to reduce this damage. Hydrological models linking the rainfall and the streamflow in a basin of a river and using the smart technologies will help to overcome such problem also and resulting in reducing the total damage in river basin including the damage of the agricultural land. This is attributed to extra measures taken for protection of the agricultural land from the flooding. In the present study a basin model was formulated to simulate the flooding in a river basin. The basin model was based on linear relationship between the rainfall and the runoff. The basin model is a black box distributed model in which the rainfall and runoff in each subcathment of the river basin was simulated separately and then combined together to get the total response of the simulated river basin. Linggi River system in Seremban, Negeri Simbilan was chosen as a case study. The total catchment area of the Linggi River system is 127 km2 . The basin model was calibrated and verified using the available data for Linggi River system. Testing of the basin model using the Theil’s technique showed that the model output is in agreement with historical record of the Linggi River. Therefore the basin model can be applied for the flood management in the Linggi River basin.